2020
DOI: 10.1016/j.trd.2020.102332
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between built environment and metro ridership at station-to-station level

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(81 citation statements)
references
References 38 publications
4
74
0
3
Order By: Relevance
“…With regard to different regression models, taking into account the overdispersion of ridership, nonlinear relationship between the independent and the dependent variables, and spatial error model could generate better results than the multiple linear regression based on adjusted R 2 . In particular, the nonlinear model, GAM, has both lower MAPE value and higher adjusted R 2 , which is consistent with the findings of existing studies [17,23,42].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…With regard to different regression models, taking into account the overdispersion of ridership, nonlinear relationship between the independent and the dependent variables, and spatial error model could generate better results than the multiple linear regression based on adjusted R 2 . In particular, the nonlinear model, GAM, has both lower MAPE value and higher adjusted R 2 , which is consistent with the findings of existing studies [17,23,42].…”
Section: Discussionsupporting
confidence: 90%
“…Many studies have found that higher population density and employment density increase the ridership [3,[19][20][21]. Built environment factors around the station such as density, diversity, and design have a significant effect on the ridership of urban rail [14,[22][23][24]. e attributes of the station itself also have a significant impact on ridership, with transfer and terminal stations associated with higher ridership [25][26][27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The well-supplied medical service is associated with high commercial prosperity at the community level, which indirectly and positively affects the COVID-19 cluster size. Community transportation infrastructure is the key essence of developing convenient commercial and medical facilities that in general ensure citizen’s quality of life ( Peng, Feng, & Timmermans, 2019 ; Peng, Feng, & Timmermans, 2019 ; Gan, Yang, Feng, & Timmermans, 2020 ). However, when it comes to the prevention and control of contagion, the well-developed built environment with high population density is prone to a high transmission rate of the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most previous studies focused on the properties of the node (station) including inflow, outflow, and visitation frequency, while a small body of prior studies paid attention to the properties of linkage between stations such as trip displacement and OD (origin to destination) flows. However, the OD flows are more conductive to understand human mobility characteristics from a space-time perspective [16]. Meanwhile, few existing studies are attentive to whether the transport properties are different during different time periods (e.g.…”
Section: Introductionmentioning
confidence: 99%